2019
DOI: 10.12968/jpar.2019.11.10.434
|View full text |Cite
|
Sign up to set email alerts
|

Clinical decision making and the challenges of responding to mental health needs

Abstract: The paramedic service responds to emergency calls for a variety of reasons, many relating to mental health concerns. This qualitative study aims to explore the views and experiences of student paramedics in relation to clinical decision making for mental health calls. Focus groups were used to investigate the participants' perspectives. Thematic analysis was used to organise data and identify key issues. Findings suggested some disparity between what paramedic students were prepared for and the reality of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…More specifically, paramedics consider EMS to lack the appropriate resources to help patients with mental illness (McCann et al, 2018a) or that mental illness is not a life-threatening condition and, therefore, the use of emergency services in these situations is inappropriate (Ford-Jones and Chaufan, 2017;Prener and Lincoln, 2015). Two themes emerged across several studies in regard to the source of paramedics' frustration: one, that attending calls related to mental illness draws resources away from "more important" jobs (Rees et al, 2018;Hutchison et al, 2019) and two, that the EMS system was not appropriately resourced to help patients with mental illness without physical illness or injury (Cook, 2020;McCann et al, 2018a). Rees et al (2018) reported common problems for paramedics when attending calls related to mental illness include compassion fatigue as a result of attending the same type of job (e.g.…”
Section: Knowledge Of Mental Health Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…More specifically, paramedics consider EMS to lack the appropriate resources to help patients with mental illness (McCann et al, 2018a) or that mental illness is not a life-threatening condition and, therefore, the use of emergency services in these situations is inappropriate (Ford-Jones and Chaufan, 2017;Prener and Lincoln, 2015). Two themes emerged across several studies in regard to the source of paramedics' frustration: one, that attending calls related to mental illness draws resources away from "more important" jobs (Rees et al, 2018;Hutchison et al, 2019) and two, that the EMS system was not appropriately resourced to help patients with mental illness without physical illness or injury (Cook, 2020;McCann et al, 2018a). Rees et al (2018) reported common problems for paramedics when attending calls related to mental illness include compassion fatigue as a result of attending the same type of job (e.g.…”
Section: Knowledge Of Mental Health Treatmentmentioning
confidence: 99%
“…This "medicallyoriented" culture may then contribute to poor attitudes towards people who use EMS for mental illness (McCann et al, 2018a(McCann et al, , 2018b. In support of this view, Hutchison et al (2019) noted a considerable disparity between student paramedics' perceptions of the role of paramedics and the reality of the profession. Specifically, student paramedics reported that the role of paramedics was primarily in the preliminary on-scene treatment of physical illness and injury (Hutchison et al, 2019).…”
Section: The Limitations Of Current Undergraduate Training Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also evidence that many paramedics have negative attitudes towards emergency services' current role as a frontline provider of treatment for patients experiencing mental illness (McCann et al, 2018a). Negative attitudes towards patients experiencing mental illness present in paramedic students as well, with many reporting beliefs that the paramedics' role is emergency treatment of physical illness and injury (Hutchison et al, 2019). These attitudes may be underpinned by the design of undergraduate paramedic courses, whereas little as 4% of total student learning is devoted to mental illness (O'Meara et al, 2017).…”
Section: Introductionmentioning
confidence: 99%